Two decades of adjustment and agricultual development in Latin America and the Caribbean - Spoor, Max (ECLAC SantiagoCL, 2000)
Analyses two decades of econoic adjustment in Latin America and the Caribbean, focusing on its impact on the agricultural (and in some cases, the rural) sector.